Complete mitochondrial DNA sequences reveal the maternal genetic structure of Vietnamese Austroasiatic-speaking Bana, Hre, and Mnong populations - Dinh Huong Thao; La Duc Duy, Nong Van Hai, Nguyen Thuy Duong (Vietnam Journal of Science, Technology and Engineering, 2026)
Austroasiatic, a major ethnolinguistic family in Vietnam, accounts for 90% of the census population size. Apart from the majority Kinh group, 24 other Austroasiatic minorities account for 4.67% of the population, many of which remain understudied. Here, the genetic characteristics of three Vietnamese Austroasiatic ethnic groups (Bana, Hre, and Mnong) were investigated by analysing the complete mitochondrial DNA (mtDNA) of 119 individuals. A total of 6,361 polymorphic sites were identified, with Bana exhibiting the highest molecular diversity (53.64±3.51 variants per individual). Compared to hypervariable segments (HVS), complete mtDNA sequences enhanced phylogenetic resolution and accuracy. The maternal haplogroup profile consisted of 40 lineages, with 32 of the detected lineages being population specific, six shared between two populations, and two shared among all populations. The macro-haplogroup components included B, C, F, M, N, R, and Z, with 66-80% of each population assigned to haplogroups B and M. The most prevalent haplogroups were M20 (14.29%), B5a1a (6.72%), and M74b1 (6.72%). While lineages of haplogroup F were relatively more frequent in Bana and Hre, lineages of N were exclusive to Mnong, highlighting haplogroup distinctions within the Vietnamese Austroasiatic family of the Central Highlands. These findings contribute to reconstructing the complex history of migration and settlement in Vietnam.